Does the addition of targeted prostate biopsies to standard systemic biopsies influence treatment management for radiation oncologists?. (4th May 2015) - Kamrava, Mitchell; Hegde, John V.; Abgaryan, Narine; Chang, Edward; Le, Jesse D.; Wang, Jason; Kupelian, Patrick A.; Marks, Leonard S.
Abstract : Objectives: To study the management impact that magnetic resonance imaging (MRI)‐guided targeted prostate biopsies could provide relative to using only non‐targeted systematic biopsies in men with clinically localized prostate cancer (PCa). Patients and Methods: A consecutive series of untreated men undergoing Artemis (MRI‐ultrasonography fusion) biopsies between March 2010 and June 2013 was evaluated in this retrospective, institutional review board‐approved study. Fusion biopsy included MRI‐targeted and systematic sampling at the same session. 3‐Tesla multiparametric MRI was performed at a median of 2 weeks before biopsy. Patients were included if ≥1 systematic core was found to harbour PCa. The impact of the information obtained from targeted vs systematic biopsies was studied with regard to the following: Gleason score (GS), National Comprehensive Cancer Network (NCCN) risk reclassification, cancer core length, percentage of core positive for tumour involvement, and percentage of positive biopsy cores. Results: The study sample included 215 men (mean ±sd age 66 ± 8 years). The median (range) prostate‐specific antigen (PSA) was 6.0 (0.7–181) ng/mL. The mean number of total biopsy samples was 18 (12 systematic and six targeted samples). Of 215 men, 34 (16%) had a higher GS on targeted vs systematic biopsy. A total of 21/183 men (12%) were stratified into a higher NCCN risk group when incorporating targeted biopsy GS results and 18/101 men (18%) were upgraded to intermediate‐ or high‐risk from the low‐risk group. Among the 34 men whose cancer severity was upgraded, increases in cancer core length, percentage of tumour involvement and percentage of cores involved were all statistically significant ( P  < 0.01). Conclusion: Targeted prostate biopsy provided information about GS, NCCN risk and tumour volume beyond that obtained in systematic biopsies, specifically increasing the proportions of men in the intermediate‐ and high‐risk groups. Such men may be recommended for additional treatments (pelvic nodal irradiation or hormonal therapy). The appropriateness of changing treatment because of targeted biopsy results is still unclear.